Alcohol Binge Drinking-Induced ST-Segment-Elevation Acute Coronary Syndrome - Steven Swarath MBBS; Nicole Maharaj MBBS; Dayna Lalchansingh MBBS, MPH; Rajeev Seecheran MBBS, MHA; Valmiki Seecheran MBBS, MSc; Abel Yoandri Leyva Quert MD; Naveen Anand Seecheran MBBS, MD, MSc, FACP, FRCP (E) (SAGE Publishing, 2022)
We present the case of a 26-year-old man, without any apparent cardiovascular risk factors, who experienced an ST-segment-elevation acute coronary syndrome after binge drinking high-proof alcohol, which was successfully managed with primary percutaneous coronary intervention and comprehensive, guideline-directed medical therapy.